A6.15 Characterisation of systemic lupus erythematosus subgroups with features of antiphospholipid or sjögrens´s syndrome utilising affinity proteomics. (24th February 2016) - Idborg, H; Zandian, A; Gustafsson, JT; Gunnarsson, I; Svenungsson, E; Nilsson, P; Jakobsson, PJ
Abstract : Background and objectives: Systemic Lupus Erythematosus (SLE) is an autoimmune disease that covers a wide range of phenotypes, from subtle symptoms to life-threatening conditions. The heterogeneous presentation of SLE is a major obstacle in clinical trials and the lack of biomarkers also hampers accurate diagnosis and choice of treatment. In this study we explored biochemical pathways in two suggested subgroups of SLE utilising affinity proteomics in order to characterise subgroups and identify biomarkers for personalised medicine. Materials and methods: We have utilised Karolinska SLE cohort consisting of 320 well-characterised SLE patients and 320 individually matched population based controls in a cross-sectional study. SLE subgroups were defined only based on patients´ autoantibody profile: an Antiphospholipid Syndrome-like (APS-like, n = 55) and a Sjögren's Syndrome-like (SS-like, n = 58) subgroup. Based on literature and clinical knowledge we have made a targeted selection of 281 proteins targeted by in total 367 antibodies from the Human Protein Atlas. Antibodies were covalently coupled to colour-coded magnetic beads. EDTA-plasma samples were labelled with biotin and screened in a 384 bead array format. The read-out was made by adding a streptavidin fluorophore and using the Luminex-technology. Results: We identified differences in protein profiles comparing APS-like and SS-like SLE subgroups: The top most significantly different proteins were Integrin beta 1 (p = 9.8e-8, Log2 fold change=1.5), renin (p = 2.7e-5, Log2 fold change=0.5), glutamic-oxaloacetic transaminase 1 (p = 2.9e-5, Log2 fold change=0.5) and Apolipoprotein M (p = 3.4e-5, Log2 fold change=0.3) that all were increased in SS-like SLE, while Apolipoprotein H (β2-GPI, p = 6.6e-5, Log2 fold change=-0.3) were increased in the APS-like subgroup. Conclusions: The two suggested SLE subgroups were defined exclusively on autoantibody profile as the APS-like and the SS-like subgroups. Our results demonstrate that the two subgroups differ in their protein profiles and that these observations indicate underlying pathogenic differences between SS-like and APS-like SLE. A common aetiology of the presence of β2-GPI in both APS and in APS-like SLE is suggested. Therefore, we believe that stratification of SLE patients should be further explored towards personalised medicine.